South toward home : travels in Southern literature - Eby, Margaret (W.W. Norton & Company, 2015)
"A literary travelogue that ventures deep into the heart of classic Southern literature. As the writer Elif Batuman did for Russian literature in The Possessed, Margaret Eby does for Southern literature in this charming book of literary exploration. From Mississippi (William Faulkner, Eudora Welty, Richard Wright, Barry Hannah) to Alabama (Harper Lee, Truman Capote) to Georgia (Flannery O'Connor, Harry Crews) and beyond, Eby--herself a Southerner--travels through the Deep South to the places that famous Southern authors lived in and wrote about. South Toward Home reveals how they took these places and the lives of their inhabitants and transmuted them into lasting literature. Whether meeting the man in charge of feeding Flannery O'Connor's peacocks in Milledgeville, peering into Faulkner's liquor cabinet, or seeking out John Kennedy Toole's iconic hot dog vendors in New Orleans, Eby combines biographical detail with expert criticism to deliver a rich and evocative tribute to the literary South" --Resumé vydavatele
Brožované vydání 2016
Keywords: americká literatura -- Spojené státy americké (jižní oblast); literárněvědné rozbory; American literature -- United States, Southern; literary criticism and history; eseje; essays